293 NITROUS OXIDE CRYOBALLOON ABLATION IS A SAFE, EFFECTIVE AND DURABLE ENDOSCOPIC TREATMENT FOR DYSPLASTIC TREATMENT-NAïVE AND PREVIOUSLY-ABLATED NEOPLASTIC BARRETT'S ESOPHAGUS. (14th September 2020) - Dbouk, M; Brewer, O; Shin, E; Ngamruengphong, S; Voltaggio, L; Montgomery, E; Canto, M
Abstract:  : Nitrous oxide cryoballoon (CB) ablation can effectively and safely eradicate dysplasia and intestinal metaplasia (IM) in patients with dysplastic BE but the durability of treatment effect is unknown. We evaluated the safety, efficacy and durability of CB ablation for complete eradication of dysplasia and IM Methods: We analyzed the outcomes of consecutive BE patients treated with CB at a single academic medical center for dysplastic BE. We excluded patients with adenocarcinoma and those treated primarily with radiofrequency ablation (RFA). CB ablation was applied to all visible BE using the CB focal ablation system and default cryogen dose of 10 seconds, after eradication of neoplastic-type lesions with endoscopic mucosal resection (EMR). Primary endpoints were complete eradication of dysplasia (CE-D) and intestinal metaplasia (CE-IM) at 1, 2, 3, 4 years. Kaplan-Meir analysis was performed to assess durability where any recurrence was considered a failure. Results: 70 patients (HGD = 64%; 65.7% = treatment-naive) were followed up for median of 27.4 months. CE-D and CE-IM at 1 year were 96.7% and 73.8%, respectively. The median number of CB sessions to achieve CE-IM at 1 year was 3 (IQR 2-3.5). The rates of CE-D and CE-IM allowing for re-treatment with CB or "touch-up" APC were above 90% at 2, 3 and 4 years, with no difference between treatment-naïve and previously-ablated patients. The durability of CB response in patients who achieved CE-D or CE-IM at 1 year followed until last follow-up or recurrence of dysplasia or IM are presented in Figure 1. Conclusion: Recurrence rate of IM after initial CB eradication is low patient with no patients progressing to cancer or beyond their baseline dysplasia grade. CB ablation has high efficacy, safety, and durability for eradicating dysplasia and intestinal metaplasia in dysplastic BE as a primary or rescue therapy.